(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the current scenario of educational institutions, multimedia has dig up its own kind of space in some or the other way as a tool of educational technology. Multimedia has overcome the barriers of time and space and provides evidence to be accepted as an anytime and anywhere tool for educating multi-disciplinary masses. Multimedia is used to present information in many exciting ways by combining hypermedia techniques with instruction. Good presentations can be created when they are based on cognitive objectives that focus on the learning of topics at different levels of comprehension. Interactive multimedia has the potential to create high quality learning environments which actively engage the learner, thereby promoting deep learning. However there is growing evidence that the potential of Interactive Multimedia enables designers to choose from a range of media elements to convey a particular message, whether that is text to display simple instructions or moving images to represent a process. Multimedia technology empowers the educational process by means of increased interaction between teachers and the students. In this Article, we overviewed the Concept of Multimedia usage in Educational Settings in detail.